2020
DOI: 10.1016/j.tate.2020.103149
|View full text |Cite
|
Sign up to set email alerts
|

How and why are educators using Instagram?

Abstract: Social media are commonplace in many educators’ lives, but their Instagram activities have received no prior attention in the empirical literature. We therefore created and disseminated a survey regarding educators’ Instagram use. Analyses of 841 responses suggested participants were generally intensive users of Instagram who engaged in the exchange of both professional knowledge and wisdom, as well as affective support. In addition to identifying benefits to Instagram use, some participants offered critiques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 74 publications
2
109
0
31
Order By: Relevance
“…Digital technologies have become integral to many SDL activities (Merriam & Baumgartner, 2020), especially in helping educators to self‐direct more of their professional learning and connect with colleagues beyond their individual schools (Beach, 2017; Carpenter & Krutka, 2015; Macià & García, 2016). In particular, educators' use of social media platforms such as Twitter (Staudt Willet, 2019), Facebook (Ranieri, Manca, & Fini, 2012), Pinterest (Schroeder, Curcio, & Lundgren, 2019) and Instagram (Carpenter, Morrison, Craft, & Lee, 2020) for SDL has become quite common. Although SDL is often associated with individual pursuits such as independent study, social media can also facilitate learning that features both autonomy and collaborative elements (Kim, Lee, & Park, 2019; Lantz‐Andersson et al ., 2018).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Digital technologies have become integral to many SDL activities (Merriam & Baumgartner, 2020), especially in helping educators to self‐direct more of their professional learning and connect with colleagues beyond their individual schools (Beach, 2017; Carpenter & Krutka, 2015; Macià & García, 2016). In particular, educators' use of social media platforms such as Twitter (Staudt Willet, 2019), Facebook (Ranieri, Manca, & Fini, 2012), Pinterest (Schroeder, Curcio, & Lundgren, 2019) and Instagram (Carpenter, Morrison, Craft, & Lee, 2020) for SDL has become quite common. Although SDL is often associated with individual pursuits such as independent study, social media can also facilitate learning that features both autonomy and collaborative elements (Kim, Lee, & Park, 2019; Lantz‐Andersson et al ., 2018).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…First, one should note the review of research from 2009-2018 that confirms the interest in online education in general [7]. Some authors describe social networks and messengers as a "digital educational network for teaching and learning" [8] and cite data that teachers use such networks for self-education and professional communication with colleagues [9][10][11][12][13]. Students also use social media and messengers for educational purposes, including collaborative work [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…According to information gathered from Pew Studies on how teens engage with social media, Auxier (2020a) found that 72% of teens use Instagram and it “ranks as the second most popular platform among Americans in this age group” (para 6). Social media should be leveraged as a pedagogical tool to be a classroom connector between course content and the visual and digital literacy of the DN student (Auxier, 2020b; Carpenter et al., 2020; Stephens & Gunther, 2016). Today's teachers must learn to communicate in the language and style of their students.…”
Section: Literature Reviewmentioning
confidence: 99%